101k views
2 votes
PPPPPPPPPPPLLLLLLLLLLLLLLLLZZZZZZZZZZZZZZ

PPPPPPPPPPPLLLLLLLLLLLLLLLLZZZZZZZZZZZZZZ-example-1
User Estmatic
by
5.5k points

1 Answer

5 votes
Easiest way is if you substitute each point (x,y) into each set of equations and both points work for both equations in the system of equations, then it is the correct answer

Otherwise substitute one equation for y in the other equation:
2x + 6 = x^2 + 5x + 6
-2x - 6. -2x -6
0 = x^2 + 3x. Factor
0 = x (x + 3)
Solve: x = 0. x + 3 = 0. ——> x = -3. Substitute into one original equation to get y value for
y = 2x + 6.
y = 2(0) + 6. y = 2(-3) + 6
y = 6. y = -6 + 6 —-> y = 0
(0 , 6) And. (-3 , 0)

User Kara Brightwell
by
4.8k points